2015
DOI: 10.3109/09537104.2015.1072147
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin response: Differences in serum thromboxane B2 levels between clinical studies

Abstract: Serum thromboxane B2 (TxB2) is a specific marker of platelet inhibition by aspirin. Yet, TxB2 levels differ by up to 10-fold between some aspirin-treated patient cohorts. This study aimed to identify factors responsible for differences in serum TxB2 between cohorts in the ADRIE study (n = 657) and the BOSTON study (n = 678) of aspirin-treated cardiovascular patients originally tested with different ELISA assays. TxB2 levels were assessed in representative subgroups of the two cohorts (34 samples in BOSTON and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…A statistically-significant difference, albeit minimal (~6 %), is already observed after a delay of 5 min, while beyond 10 min, sTXB 2 values decay exponentially, rather than linearly, as shown in ▶ Figure 1. This pre-analytical bias seems quite relevant and is independent of the sensitivity and specificity of the analytical assay used to measure sTXB 2 . Our data showing a good agreement between our EIA and LC/MS-MS determinations (▶ Figure 2) are consistent with a previous similar comparison between an immunoenzymatic assay different from the one we used which was also compared to LC/MS-MS (15).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A statistically-significant difference, albeit minimal (~6 %), is already observed after a delay of 5 min, while beyond 10 min, sTXB 2 values decay exponentially, rather than linearly, as shown in ▶ Figure 1. This pre-analytical bias seems quite relevant and is independent of the sensitivity and specificity of the analytical assay used to measure sTXB 2 . Our data showing a good agreement between our EIA and LC/MS-MS determinations (▶ Figure 2) are consistent with a previous similar comparison between an immunoenzymatic assay different from the one we used which was also compared to LC/MS-MS (15).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, a simulated delay in starting 37 °C incubation, reduced the relative percentage of aspirin 'non-responders' by 22 % to 52 %, depending on the response threshold (▶ Figure 3). This might have contributed to some large discrepancies of sTXB 2 observed among different studies (15), as well as to different clinical characteristics of poorly-responsive populations (11,14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a reproducible implementation of this procedure in multicenter studies might face practical hurdles, such as logistic delays between blood withdrawal from patients and access to a thermostatic bath, as well as the lack of appreciation of the time- and temperature-dependence of TXB 2 production during blood clotting. Consistent with this expectation, a comparison of serum TXB 2 values in two large, multicenter cohorts of aspirin-treated patients 45 , 46 showed up to 10-fold difference in median TXB 2 levels (7 and 0.6 ng/ml in the ADRIE 46 and BOSTON 45 studies, respectively) that could not be explained by patient characteristics or analytical biases 47 . Two recent in vitro studies showed that even a minor delay in starting 37 °C incubation can time-dependently underestimate serum TXB 2 levels 17 , 48 , and thus potentially account for variable aspirin responsiveness across studies and centers.…”
Section: Study Organization: Feasibility and Implementation Of The Sementioning
confidence: 61%
“…Similarly, serum thromboxane levels are an indicator of platelet inhibition by aspirin and can thus be used for epidemiological studies on the effects of aspirin (Reny et al , ; Zantek et al , ). However, measurement methods for serum thromboxane need to be standardized to produce consistent results across studies (Brun et al , ).…”
Section: Lipid Mediators In Body Fluidsmentioning
confidence: 99%